Equivalence Partitions pada BlackBox Testing terhadap Sistem Pemberdayaan Pemerataan UMKM - Marfuah, Marfuah; Adam, Steffi (Teknik Informatika Universitas Pamulang, 2021)
One of the important stages in the development of a system is testing. This stage is to ensure that the system that has been built is of good quality. The testing technique commonly used is blackbox testing. BlackBox testing to check whether the system interface functions are appropriate or not. The SMME equity empowerment system with the SIOSTIUM domain has been completed. So, the next stage is to check the system, whether the function of each form is running according to the program that has been used. Thus the blackbox testing technique used in this study is Equivalence Partitions. The way the Equivalence Partitions technique works is to see based on the input data on each form for testing based on its function. Based on the testing in this study, it was concluded that the quality of the MSME equity empowerment system was in accordance with the expected function.